2010
DOI: 10.1530/eje-10-0116
|View full text |Cite
|
Sign up to set email alerts
|

Primary tumour size is a prognostic parameter in patients suffering from differentiated thyroid carcinoma with extrathyroidal growth: results of the MSDS trial

Abstract: Objective: The Multicentre Study Differentiated Thyroid Cancer (MSDS) collective represents a well-defined group of patients with thyroid carcinomas with extrathyroidal extension. The aim of the present study was to evaluate the relationship of the primary tumour size with clinicopathological features as well as the outcome of patients with minimum and extensive extrathyroidal growth (pT3b-and pT4a-tumours; UICC 2002/2003, 6th ed). Methods: The tumour diameter was available in 324 out of 351 MSDS patients (244… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
23
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 20 publications
5
23
0
3
Order By: Relevance
“…The prevalence of ETE in PTC varies from 5% to 55.3%, and larger tumors are associated with an increased likelihood of ETE [1,3,18,[20][21][22]. In the present study, ETE was found in 49.2% (minimal ETE 41.7%, maximal ETE 7.5%) of patients with PTC, which is comparable to findings in other studies.…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of ETE in PTC varies from 5% to 55.3%, and larger tumors are associated with an increased likelihood of ETE [1,3,18,[20][21][22]. In the present study, ETE was found in 49.2% (minimal ETE 41.7%, maximal ETE 7.5%) of patients with PTC, which is comparable to findings in other studies.…”
Section: Discussionsupporting
confidence: 88%
“…[14,15] The reported prevalence of PTC with ETE varies, ranging from 2 to 45%, with progressively bigger tumors in PTC being associated with increased likelihood of ETE. [1,[3][4][5]7,8,[16][17][18] Similarly, an increasing number of studies support the present finding that PTMC displays evidence of ETE and/or nodal metastasis. [19][20][21][22] The prevalence of ETE in PTMC is similar to PTC, ranging from 2 to 52% and the increasing frequency of ETE is accompanied by the increasing tumor size in PTMC, as in PTC.…”
Section: Discussionsupporting
confidence: 76%
“…[19][20][21][22] The prevalence of ETE in PTMC is similar to PTC, ranging from 2 to 52% and the increasing frequency of ETE is accompanied by the increasing tumor size in PTMC, as in PTC. [9,12,18,[23][24][25][26][27][28][29][30] In this study, the prevalence was 28.0% (91/325) and the frequency of ETE also increased with increasing tumor size. The collective observations suggest that PTMC may be an early-detected form of PTC, rather than a different disease entity, which may have been described previously as an indolent tumor.…”
Section: Discussionmentioning
confidence: 78%
“…Recurrence is found in 16%-35% of DTC patients after initial surgery (19,20), and recurrent DTC cells often exhibit negative 131 I uptake and positive findings on 18 F-FDG PET/CT due to cell dedifferentiation (6,21). Furthermore, T stage, presence of nodal metastasis, and tumor size are prognostic factors for DTC that reflect the aggressiveness of cancer cells (16,17,22,23). A previous study has already shown that glucose transporter 1 expression increased with escalating dedifferentiation and aggressiveness of thyroid cancer cells (24).…”
Section: Discussionmentioning
confidence: 99%